Risk Characterization of Treatment Histories and Comorbidities Regarding Tuberculosis Treatment Status in West Sumatra Province 2020-2021 - Sari, Novita; Djafri, Defriman; Ramadhani, Mery (LPPM Universitas Prima Nusantara Bukittinggi, 2023)
Background: Tuberculosis (TB) is the leading cause of death among bacterial infectious diseases worldwide, and Indonesia is the second country with the highest TB burden.Objective: The treatment history and comorbidities of TB disease play a significant role in determining the appropriateness of therapy and the duration of treatment for patients. The objective is to identify the factors that influence the incidence of first molar caries.Methods: This study employs an analytic case-control design with a retrospective cohort methodology. 161 RO TB patients and 161 SO TB patients comprised the total sample size. Statistical analysis of this investigation utilizing R and R Studio.Result: In this study, there was a correlation between gender (p-value 0.006 and odds ratio 1.89), contact investigation (p-value 0.001 and odds ratio 0.23), new TB (p-value 0.001 and odds ratio 0.05), TB recurrence (p-value 0.001 and odds ratio 19.0), TB failed treatment (p-value 0.007 and odds ratio 16.4), and pH-saliva (p-value 0.0001 and odds ratio 21.250). In contrast, risk factors such as absenteeism, diabetes, and HIV were not associated with TB treatment status (p-value > 0.05). Age, investigation of contact, and TB recurrence were the predominant factors associated with TB treatment status, as determined by multivariate analysis.Conclusions: Several factors, including gender and treatment history (new TB, Relapsed TB, Failed TB), influence the status of TB treatment in West Sumatra Province. These are important factors that must be considered and asked by TB officers at health facilities before the patient undergoes an examination of suspected samples and information to provide appropriate medical therapy to TB patients in health facilities.